2015
DOI: 10.1080/02619768.2015.1056911
|View full text |Cite
|
Sign up to set email alerts
|

Student teachers’ perceptions of feedback as an aid to reflection for developing effective practice in the classroom

Abstract: Since Schön's influential work on reflective practice reflection has been prioritised in teacher education programmes internationally. The research described in this paper examined the development of postgraduate student teachers' reflective processes in their first school placement. 25 students were asked to write an account of their evolution in an area of their teaching, and how they were supported to evaluate lessons and reflect on their practice. Subsequently, a sample was interviewed to explore themes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
1
13
0
4
Order By: Relevance
“…Thus, transformative reflection allows the teacher candidate to challenge assumptions and beliefs that also lead to choosing appropriate pedagogies in the classroom that are responsive to students' diverse needs (Carrington & Selva, 2010). Accordingly, teacher candidates examine their thoughts and feelings and move toward a plan of action for teaching and learning (Crichton & Valdera, 2015).…”
Section: Reflective Practice In Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, transformative reflection allows the teacher candidate to challenge assumptions and beliefs that also lead to choosing appropriate pedagogies in the classroom that are responsive to students' diverse needs (Carrington & Selva, 2010). Accordingly, teacher candidates examine their thoughts and feelings and move toward a plan of action for teaching and learning (Crichton & Valdera, 2015).…”
Section: Reflective Practice In Teacher Educationmentioning
confidence: 99%
“…For example, reflective practice can lead to a committed effort to use appropriate pedagogies that demonstrate an understanding of student cultures (Carrington & Selva, 2010). Thus, teacher candidates examine their thoughts and feelings and move toward a plan of action to promote improvement for teaching and learning (Crichton & Valdera, 2015). The notion of reflection and its connection to teaching competence moves the teacher to a deeper level of transformative learning (Lawrence-Wilkes, 2014) that instills a sense of professional autonomy and allows educators to make educational decisions on behalf of their students.…”
Section: Introductionmentioning
confidence: 99%
“…Student teachers often view university supervisors as possessing an assessment role rather than an assistance role as they assign grades (Borko & Mayfield, 1995). Conversely, student teachers often view mentors, such as cooperating teachers, as a main source of feedback and assistance (Crichton & Gil, 2015). Both provide a valuable perspective to the student teacher experience.…”
Section: Current Practices In Student Teacher Feedbackmentioning
confidence: 99%
“…Lastly, it was determined that social sciences teachers use encouraging and motivating statements as well as positive and constructive statements. It was confirmed that teachers use encouraging and motivating statementsto make students understand that they are successful, to make them ambitious, and to contribute their level of success [40,41,42].…”
Section: Discussionmentioning
confidence: 82%